CT-guided Foramen Ovale Injection of Mesenchymal Stem Cells: First Human Case Report of Trigeminal Neuralgia Relief - Candido, Kenneth; Prodromos, Chadwick; Nenchev, Kristian (Current Stem Cell Research & Therapy, 2025)
Introduction/ObjectivesTrigeminal neuralgia (TN) is an extremely painful condition without an established treatment other than symptom suppressive medications or temporary relief from corticosteroid injections. Mesenchymal Stem Cells (MSCs) have demonstrated the ability to enhance healing and reduce inflammation and pain without side effects. Our objective was to evaluate the safety and efficacy of CT-guided foramen ovale MSC injection in the treatment of TN.Case ReportA 48-year-old woman presented with a 22-year history of severe TN. Previous treatments, including microvascular decompression, acupuncture, chiropractic adjustment, and hypnotism had failed. Medications decreased pain but produced severe bothersome mental clouding. After proper informed consent, the patient elected trigeminal nerve injection in the foramen ovale with AlloRx (vitrobiopharma.com Golden Colorado) umbilical cord-derived mesenchymal stem cells (MSCs). An experienced pain specialist with previous experience using CT guidance with sedation to inject the trigeminal nerve in the foramen ovale with corticosteroids, performed the injection using 20 million MSCs. The patient had no adverse events or complications related to the treatment. At 1 month post treatment the patient reported dramatically reduced pain/tingling, and no longer needed medication resulting in resolution of her mental clouding. At 12 months post-treatment, some symptoms recurred, but the patient maintained substantial cognitive improvements and required a reduced dose of medication.ConclusionWe have demonstrated for the first time that CT guided MSC injection into the foramen ovale results in significant improvement in trigeminal neuralgia without side effects.
Keywords: trigeminal neuralgia